The evaluation of clinical isolates of Mycobacterium tuberculosis in the murine and guinea pig infection models - Caraway, Megan L., author; Orme, Ian, advisor; Lenaerts, Anne, committee member; Callan, Robert, committee member (Colorado State University. Libraries, 2011)
Globally the tuberculosis epidemic continues unabated, affecting over nine million people a year, with more than half a million of these cases being resistant to multiple drugs. Multiple drug resistant tuberculosis (MDR-TB) is becoming a growing problem to the world's population. Despite this growing problem, very little research is being focused on MDR-TB. One basic question not yet addressed is how drug resistance affects virulence levels. A hypothesis, originating from classical studies of Mitchison, is that drug resistance results in a lower virulence level. Using the murine and guinea pig models of infection, I studied the ability of multiple isogenic pairs of Mycobacterium tuberculosis to grow in these particular animal models, in order to determine if acquired drug resistance increased or decreased the virulence of the drug resistant strain. In the murine model there was no discernable relationship between the drug resistance of a given strain and its virulence. Instead, isogenic drug resistant strains exhibited a range of virulence. Interestingly, the opposite was seen in the guinea pig infection model. In this model, it was observed that the drug resistant strain of the isogenic pair caused less severe disease and pathology. Drug resistance is not the only cause for concern in the ever continuing tuberculosis epidemic. Many strains that are associated with outbreaks around the world are being classified as either high or low transmission strains. High transmission strains are thought to be associated with increased rates of infections and higher virulence, the latter driving the former. Low transmission strains are the opposite; while they have been known to cause disease the numbers of cases where these strains have been identified appear to be fewer. I examined the virulence and pathogenicity of two strains selected for apparent high versus low transmission patterns, recently seen in a tuberculosis outbreak within the Chinese community of San Francisco, CA, USA that were typed as being W - Beijing strains. My studies did not support the hypothesis that high transmission strains have a higher virulence level.